The Influence of Attitudes, Norms and Control Subyetif Interests Attitudes to Using Internet Banking In BRI Kotamobagu Branch - Roring, Ferdy (Jurnal Teknik Informatika, 2012)
Commercial banks have introduced internet-based on banking system to improved operations and reduced costs. Internet banking is one form of service were started a lot of products offered by commercial banks in Indonesia.The sample in this study was 100 from total population 809 clients. Analysis tools used multiple linear regression, hypothesis testing using t test and F test before being tested by using multiple linear regression, previously tested using the data validity and reliability as well as testing the classical assumptions. Tests conducted with the help of SPSS software.The results showed that attitudes, subjective norms and behavioral control affect the interest of using internet banking either partially or simultaneously. The relationship between the variables X and Y is strong, while the magnitude of the influence of variable X to variable Y is equal to 38.8% while the remaining 61.2% is influenced by variables other than research. The dominant variable is the control of behavior.Increased interest of customers to use internet banking should be improved by Bank BRI Branch Kotamobagu by increasing or add information on internet banking, as most customers are still not understand about internet banking.Keywords: Attitude, Subjective Norms, Behavioral Control, Use Internet Banking Interests.